Optimizing water-use efficiency under elevated CO₂: A meta-analysis of crop type, soil modulation, and enrichment methods - Ali Mokhtar; Hongming He; Samar Attaher; Ali Salem; Muneer Alam (Agricultural Water Management)
Elevated CO2 (eCO2) significantly affect the carbon-water cycle in terrestrial ecosystems especially for gas exchange and water use efficiency (WUE). Therefore, in this study, we have conducted a meta-analysis to quantitative statistical means among studies and discuss how WUE responds to eCO2 under pathway (C3 and C4), four enrichment methods and soil types based on 124 peer-reviewed studies and 1474 observations to provide an in-depth overview of how these factors interact under future CO₂ scenarios. Key findings reveal that: (1) C₃ crops, such as potato and tomato, show significantly greater increases in WUE compared to C₄ crops like maize, with effect sizes of 13.96 and 7.02 for plant-level WUE (WUEₚ), suggesting that C₃ crops may be more advantageous in water-limited environments due to reduced photorespiration under eCO₂; (2) soil type substantially modulates WUE responses, with clay soils, due to their high water-holding capacity, demonstrating the highest WUE enhancements (effect sizes of 7.87 for WUEₚ and 12.54 for yield WUE, WUEᵧ), while sandy soils, characterized by rapid drainage, showed limited improvements; and (3) greenhouse and growth chamber studies displayed the highest WUE improvements, while FACE experiments, which better replicate real-world conditions, indicated smaller WUE increases due to environmental variability, underscoring the need for a hybrid approach that merges controlled data with field insights to develop practical, water-efficient agricultural strategies. Collectively, these findings highlight the potential for crop- and soil-specific strategies to optimize WUE under elevated CO₂, offering valuable insights for sustainable agriculture and climate adaptation.